Pengembangan Front-End Edu-Perikanan Pada Program Smart Fisheries Village Bangsring dengan Metode UCD dan UEQ - Rohman, Thoifur; Hadiq (Bulletin of Computer Science Research, 2024)
The development of the front-end Edu Fisheries in the Smart Fisheries Village (SFV) Bangsring program using User-Centered Design (UCD) and User Experience Questionnaire (UEQ) aims to improve access to and quality of fisheries education. SFV Bangsring faces specific issues such as the low level of education and awareness among the local community regarding sustainable fishing practices, as well as the ineffectiveness of previous conventional approaches. The UCD method is used to understand user needs and design an intuitive user interface, while the UEQ method is used to evaluate user satisfaction with the developed system. The development results show a significant improvement in the accessibility and quality of fisheries education, with a 40% increase in fishermen's knowledge about sustainable fishing practices and a 35% increase in user satisfaction compared to previous approaches. The evaluation with UEQ covers aspects of attractiveness, clarity, efficiency, accuracy, stimulation, and novelty, all of which show positive average score increases. This research emphasizes the importance of a user-centered approach in designing educational systems that respond to user needs, as well as the significant positive impact on improving the accessibility and quality of fisheries education, and awareness and sustainable fishing practices in the SFV Bangsring environment. The implementation of this technology is expected to continue supporting the empowerment of the fishing community through better and more sustainable education.